The contribution of the Drosophila model to lipid droplet research. - Kühnlein, R.P. (Progress in lipid research, 2011)
Intracellular lipid droplets have long been misconceived as evolutionarily conserved but functionally frugal components of cellular metabolism. An ever-growing repertoire of functions has elevated lipid droplets to fully-fledged cellular organelles. Insights into the multifariousness of these organelles have been obtained from a range of model systems now employed for lipid droplet research including the fruit fly, Drosophila melanogaster. This review summarizes the progress in fly lipid droplet research along four main avenues: the role of lipid droplets in fat storage homeostasis, the control of lipid droplet structure, the lipid droplet surface as a dynamic protein-association platform, and lipid droplets as mobile organelles. Moreover, the research potential of the fruit fly model is discussed with respect to the prevailing general questions in lipid droplet biology.